(untitled) (Biological Sciences - PJSIR, 2009)
On determining the effects of different humidity levels on the biology of mealy bug Pseudococcus longispinus (Targioni and Tozzetti), it was found that the relative humidity (RH) at 35%, 55% and 75% had no effect on pre-adult development, adult longevity, life span and fecundity of P. longispinus. The survival of pre-adult stages was minimal at 35% RH. Sex ratio was male-biased at 35% RH and female-biased at 75% RH.